Description of Scoloplos maranhensis sp. nov. (Orbiniidae, Annelida) from tropical Brazilian mangrove - Oliveira,Veronica M. (2019)
ABSTRACT A new species of orbiniid, Scoloplos maranhensis sp. nov., is described from a tropical mangrove (Quebra Pote, state of Maranhão, Brazil, 02°41.344’S; 44°12.604’W) along with a comparative table with all Scoloplos species. The main distinguishing characters of S. maranhensis sp. nov. are thorax with 12 chaetigers, neuropodia from first chaetiger, notopodia and neuropodia without papillae, conical branchiae from 12th chaetiger to the end of the body, being larger and more robust in the anterior segments. Thoracic notopodia with seven crenulated capillary chaetae and abdominal notopodia with furcated and capillary chaetae. Thoracic neuropodia rounded with two crenulated capillary chaetae and six slender-smooth hooks, abdominal neuropodia with a post-chaetal lobe and only capillary chaetae. Papillae absent from posterior parapodia; one pair of cirriform anal cirri.